FORMATION OF COMMUNICATIVE SKILLS OF FUTURE PILOT IN THE CONTEXT OF SYSTEMIC APPROACH - Бродова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
This article is devoted to the place of communicative skills in the future pilots professional readiness structure. The author has introduced his own definition of such concepts as «communicative skills of pilots», which are necessary for them and were disclosed their essence